Viscous flow flash sintering of porous silica glass - Prado, Miguel Oscar (2017)
For the first-time compacts of porous glass particles (95 wt% SiO2, 2.3% Na2O, 1.6% Al2O3) exhibiting macro-, meso- and micro-pores were densified by flash sintering, using DC electric field in the range 1000–3000 V cm− 1. The results point out the applicability of this sintering technology to glasses characterized by viscous flow sintering mechanisms. Excluding the anodic region, the specimens resulted well densified using a current limit of 2 mA mm− 2 and a dwelling time of 30 s. The obtained microstructure at the anode and at the cathode side is asymmetric, the former being characterized by the formation of Na-enriched region, the latter by the local formation of large pores (hundreds of microns). The mechanism, which triggers the flash event, appears to be associated to dielectric breakdown.